John Dewey’s emergent theory of mind: Preface to the translation of the seventh chapter, «Nature, Life and Body-Mind», from John Dewey’s «Experience and Nature» - Leonov, Андрій (Actual Problems of Mind, 2024)
This paper provides a short historical-philosophical commentary on the first Ukrainian translation of the seventh chapter, «Nature, Life and Body-Mind», from John Dewey’s Experience and Nature, first published in 1925, and which has since been regarded as Dewey’s philosophical magnum opus. This commentary includes a short history of the book, a description of its structure, as well as a brief consideration of its significance from both historical and contemporary perspectives. The paper briefly discusses the book’s main methodology, denotative method, which treats experience from a functional perspective the essence of which can be thought of as the practice-theory-practice pattern. For Dewey, implementing this method into philosophy should make the latter more practical and effective. Experience and Nature is a clear expression of Dewey’s overall metaphysics and philosophy of mind and the book’s seventh chapter is central when it comes to Dewey’s solution to the mind-body problem. Thus, the paper briefly discusses Dewey’s emergent theory of mind, which is Dewey’s metaphysical solution to the mind-body problem, and which aims at restoring the continuity between nature and experience. Since this translation is in a sense experimental, this or that terminological approach should not be understood as the ultimate truth. Thus, any constructive criticism, correctives and suggestions are welcomed. The pragmatic approach to philosophy and philosophizing is essentially fallibilist, and philosophical translation is in no way exception to that. This translation is a part of Dewey’s Experience and Nature Centennial celebration organized by Center for Dewey Studies at Southern Illinois University Carbondale.